2022
DOI: 10.1007/s40747-022-00913-4
|View full text |Cite
|
Sign up to set email alerts
|

The differential measure for Pythagorean fuzzy multiple criteria group decision-making

Abstract: Pythagorean fuzzy sets (PFSs) proved to be powerful for handling uncertainty and vagueness in multi-criteria group decision-making (MCGDM). To make a compromise decision, comparing PFSs is essential. Several approaches were introduced for comparison, e.g., distance measures and similarity measures. Nevertheless, extant measures have several defects that can produce counter-intuitive results, since they treat any increase or decrease in the membership degree the same as the non-membership degree; although each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…In research of sharaf, he found the difference between support and opposition. This research [39] encourages us to find differences among three variables.…”
Section: Literature Reviewmentioning
confidence: 76%
See 2 more Smart Citations
“…In research of sharaf, he found the difference between support and opposition. This research [39] encourages us to find differences among three variables.…”
Section: Literature Reviewmentioning
confidence: 76%
“…The outcomes of other decision-making methodologies, including the TOPSIS method proposed by Zhang et al [47], the TODIM approach developed by Ren et al [48], the distance and similarity measure introduced by Zeng et al [49], the fuzzy weighted and ordered weighted aggregation operators presented by Garg [50], and the differential measure for pythagorean fuzzy sets, are compared with the outcomes of the proposed methodology. Table 4 displays the rankings that these techniques produced [39]. Table 4 demonstrates that the suggested technique produced the same optimal alternative as the ones previously employed.…”
Section: Figure 1: Improved Technique For Mcgdmmentioning
confidence: 91%
See 1 more Smart Citation